PENGARUH KUALITAS KEHIDUPAN KERJA DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA PEGAWAI MELALUI MEDIASI KOMITMEN ORGANISASIONAL (STUDI PADA SEKRETARIAT DAERAH KABUPATEN BATANG) - Tri Laksana, Kukuh; Rozak, Hasan Abdul (Jurnal Ilmiah Telaah Manajemen, 2014)
This study is intended to examine the influence of quality of work life and Employee Engagement employee performance against mediation with Organizational Commitment on the Secretariat of the Batang Regency. In this study population which object is the minimum High School educated employees in the Secretariat of the Batang Regency. In this study the author using a purposive sampling method sampling techniques i.e. with specific consideration with the purpose of criterion samples obtained was able to explain the actual state of the object is examined. So the number of samples in this research as much as 137 respondents. Results of the study prove that the value of the coefficient of determination of 99,2%. This means that the ability of the model to explain properly the relation variable quality of working life, employee engagement and organizational commitment is 99.2% on performance while the other employees amounting to 0.8% are described for the variable outside of the model. The results of the regression analysis stated that the quality of work life and Employee Engagement a positive effect against Organizational Commitment. Quality of work life, Employee Engagement and Organizational commitment to a positive effect on performance Clerk. Test results of mediation States that organizational commitment does not mediate the quality of working life and Employee Engagement employee performance against. Keywords: quality of work life, employee engagement, organizational commitment and performance of employees